Efficient Removal of Tetracycline by Metal–Organic Framework ZIF-67 and Its Mechanism - Shengyang Zheng; Yaping Xu; Xu Yao; Chenzhe Wang; Ping Liu; Haitao Zhao; Jianbing Lu; Jing Ju (Separations, 2024)
The widespread use of tetracycline (TC) poses potential hazards to ecosystems and human health. In this study, ZIF-67 was successfully synthesized using a room-temperature static synthesis method and applied to the efficient removal of TC from water. It was shown that the maximum adsorption of TC by ZIF-67 could reach 1583.128 mg·g−1 at pH = 5.0, an initial TC concentration of 450 mg·g−1, an adsorption time of 720 min, and a temperature of 308K.The pseudo-second-order kinetic model and Langmuir’s isothermal adsorption model could describe the adsorption process better, which proved that the adsorption of ZIF-67 on TC was mainly monolayer adsorption dominated by chemisorption. Mechanistic studies showed that the adsorption process of ZIF-67 on TC was mainly through electrostatic interactions, pore adsorption, π–π interactions, and framework coordination of ZIF-67 surface cations with TC.